"(I Think) My Mother Thinks I Am, Therefore I Am". The Looking-glass Self in Maltreated Children and Adolescents - Silva, Carla (2021)
Children and adolescents with maltreatment experiences show worse representations of themselves, as compared to their nonmaltreated counterparts. According to the looking-glass self hypothesis (LGSH), individuals’ self-representations (SR) stem from interactions with significant others, reflecting associations between what significant others think of them (i.e., actual appraisals), individuals’ perceptions of significant others’ appraisals of them (i.e., reflected appraisals), and SR. However, little is known about the looking-glass self process in maltreated children and adolescents. This multi-informant study aimed to test the LGSH within the mother–child relationship with children and adolescents with maltreatment experiences. Specifically, including maltreatment experiences as copredictors, this study analyzed the mediating role of mothers’ reflected appraisals (MRA) in associations between mothers’ actual appraisals (MAA) and children/adolescents’ SR. Participants were 203 children/adolescents (52.5% boys), 8–16 years old (M = 12.6; SD = 2.49), assisted by children and youth protection committees (CYPC), their mother, and their CYPC case workers. Case workers reported on child/adolescent maltreatment, children/adolescents reported on SR and MRA, and mothers reported on MAA. A multiple mediation path analysis revealed significant mediation effects of MRA between MAA and child/adolescent SR in instrumental, social, emotional, intelligence, and opposition SR, thus supporting the LGSH in the context of child/adolescent maltreatment. Also, psychological neglect was associated to worse intelligence SR, mediated by intelligence reflected appraisals. Findings emphasize the importance of the role of MRA on maltreated children and adolescents’ SR construction process, and provide useful clues to incorporate in prevention and intervention strategies targeting maltreated children and adolescents.